Polyurethane composite material, laminated product containing the polyurethane composite material and preparation method thereof
By using PU composite materials with 35-75% reinforcing fiber and 25-65% polyurethane foam in the upper cover of the battery pack, combined with spray transfer molding and long fiber injection molding, the high cost and insufficient performance of composite materials in the prior art are solved. The problem of this problem has achieved the improvement of lightweight, mechanical strength and thermal insulation performance, and is suitable for the upper cover of the battery pack.
Patent Information
- Application Number
- CN202280007035.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-09
- Filing Date
- 2022-06-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-06-06
AI Technical Summary
The prior art is difficult to provide a lightweight, thin composite material with good mechanical properties, flame retardant and thermal insulation properties for the upper cover of the battery pack, and is costly to produce and difficult to achieve a wide range of raw material use.
Using PU composite materials consisting of 35 to 75% by weight of reinforcing fiber and 25 to 65% by weight of polyurethane foam, the two-component reaction system was prepared, combined with spray transfer molding and long fiber injection molding to prepare continuous and discontinuous A polyurethane composite material of phase fibers, and a polyurethane composite material is provided on both sides of the thermal insulation layer.
It realizes a composite material with light weight, good mechanical strength, excellent flame retardancy and good voltage resistance, and is prepared at low cost and efficiently. It is suitable for the upper cover of the battery pack, with good thermal insulation performance and electromagnetic interface shielding performance.
Smart Images

Figure GDA0005134400300000291 
Figure GDA0005134400300000301 
Figure GDA0005134400300000302
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to international application No. PCT / CN2021 / 117427 filed on September 9, 2021, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present invention relates to a novel polyurethane (PU) composite material, a method for preparing the PU composite material, and a covering product containing the PU composite material. The PU composite material comprises 35 to 75% by weight of reinforcing fibers and 25 to 65% by weight of polyurethane foam, based on the total weight of the PU composite material; wherein the reinforcing fibers comprise 75 to 100% by weight of reinforcing fibers in the form of a continuous phase and 0 to 25% by weight of reinforcing fibers in the form of a discontinuous phase, based on the total weight of the reinforcing fibers. The present invention also relates to a laminated product comprising at least one thermal insulation layer and a polyurethane composite material arranged on each side of the thermal insulation layer, a method for preparing the laminated product, and a covering product containing the laminated product. Background Art
[0004] With the development of electric vehicles, the lightweight design and capacity limitation of batteries have attracted more and more attention. At present, people mainly use stamped metal sheets as the upper cover of battery packs to protect the battery components therein. Although metal materials show good mechanical properties, their density and therefore the weight of the components are high. Therefore, it is urgent to provide a new lightweight, thin and flame-retardant component to replace the metal upper cover.
[0005] The prior art discloses injection molded parts based on polypropylene or polyamide as the upper cover of the battery pack. However, such polypropylene or polyamide material injection molding solutions are difficult to realize very large-sized parts; their injection molding requires high processing costs, high injection pressure and temperature. To date, there are no publications or patents that disclose or suggest that spray transfer molding (STM) products or long fiber injection (LFI) products such as the PU composite materials obtained therefrom can be used as the upper cover of the battery pack.
[0006] For example, US2019 / 0153185A1 discloses a sandwich component comprising a polyurethane foam core and two building material boards, which are used as non-load-bearing wall elements, outer wall cladding, and ceiling elements. Specifically, it discloses that the building board may also include fibers, textiles, or reinforcing materials, which improves the tensile strength of the building material board. However, it does not disclose or suggest that the polyurethane foam core can be modified and then used in particular in the battery field, such as as an upper cover for a battery pack. In addition, those skilled in the art should understand that polyurethane foam in the construction field is relatively thick, which hinders its use as a thinner upper cover for a battery pack.
[0007] In addition, the prior art discloses a sheet molding compound (SMC) process for preparing polyurethane foam sheets, characterized in that chopped glass fibers are impregnated with resin. However, this SMC process generally has the disadvantages of high density, thicker parts, uneven distribution of reinforcing glass fibers in the final part, and high cost of post-processing steps.
[0008] On the other hand, CN 107437631A discloses a battery module comprising a frame, a protective plate and a plurality of single cells. The protective plate comprises an expandable graphite (EG) plate and an insulating sealing film, wherein the EG plate comprises a substrate, the substrate is formed by an adhesive and EG particles distributed in the substrate, and the sealing film is a polyimide (PI) film or a polypropylene (PP) film. US20080020270A describes a secondary battery for a mobile device, which contains a film ("safety film") comprising EG and polyurethane, and a substrate film selected from polyurethane and polyethylene terephthalate. However, the products provided by the prior art have only a limited EG content, and the heat insulation effect provided thereby is limited.
[0009] Therefore, there is a continuing need to provide a composite material that has light weight, reduced thickness, good mechanical properties and flame retardancy and that can be produced in a cost-effective manner. In addition, the composite material should be easy to produce using a wide range of raw materials and provide a covering product with good electromagnetic interface (EMI) shielding properties as well as the above advantages of the composite material. In addition to the above advantages of the composite material, there is also a need to provide a product with excellent thermal insulation properties. Summary of the invention
[0010] An object of the present invention is to overcome the above-mentioned problems of the prior art and to provide a composite material which is lightweight, has good mechanical strength, good flame retardancy and excellent voltage resistance, and which can be prepared in a cost-effective manner.
[0011] Surprisingly, the inventors have found that the above objects can be achieved by a polyurethane (PU) composite material comprising 35 to 75 wt. % of reinforcing fibers and 25 to 65 wt. % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0012] The polyurethane foam is obtained from a two-component reaction system comprising the following substances:
[0013] Isocyanate component consisting of:
[0014] (a) at least one isocyanate or isocyanate prepolymer, and
[0015] The polyol component consists of:
[0016] (b) at least one isocyanate-reactive polyol,
[0017] (c) optionally a chain extender and / or a cross-linking agent,
[0018] (d) flame retardants,
[0019] (e) optionally a filler,
[0020] (f) a blowing agent,
[0021] (g) a catalyst, and
[0022] (h) optionally additives and / or auxiliaries,
[0023] wherein the reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers; and
[0024] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers.
[0025] In another aspect, the present invention relates to a method for preparing a PU composite material as described above, wherein the method comprises the following steps:
[0026] 1) providing reinforcing fibers in the form of a continuous phase;
[0027] 2) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0028] (b) at least one isocyanate-reactive polyol,
[0029] (c) optionally a chain extender and / or a cross-linking agent,
[0030] (d) flame retardants,
[0031] (e) optionally a filler,
[0032] (f) a blowing agent,
[0033] (g) a catalyst, and
[0034] (h) optionally additives and / or auxiliaries,
[0035] 3) mixing the polyol component obtained in step 2) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0036] 4) spraying or injecting the mixture obtained in step 3) onto the reinforcing fibers in the continuous phase provided in step 1) through a first nozzle or an injection head, and optionally spraying the reinforcing fibers in the discontinuous phase onto the reinforcing fibers in the continuous phase provided in step 1) through a second nozzle to obtain a sprayed or injected product;
[0037] 5) hot pressing the sprayed or injected product obtained in step 4) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0038] 6) demoulding and optional trimming;
[0039] The polyurethane composite material obtained in step 6) comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material, and
[0040] The reinforcing fibers comprise 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers;
[0041] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0042] Surprisingly, it was found that in the present application, the PU composite material as described above or the PU composite material prepared by the method as described above shows reduced weight, good mechanical strength, good flame retardancy and excellent voltage resistance. In addition, the method is carried out in a robust and easy manner. Accordingly, the PU composite material is obtained cost-effectively.
[0043] In yet another aspect, the present invention relates to a covering article comprising the PU composite material as described above or the PU composite material prepared by the method as described above.
[0044] Another object of the present invention is to provide a laminated product having light weight, good mechanical strength, good flame retardancy and good thermal insulation properties.
[0045] Surprisingly, the inventors have found that this object can be achieved by a laminated product comprising at least one insulating layer and at least two layers of a polyurethane composite material as described above, wherein the polyurethane composite material is arranged on each side of the insulating layer; wherein the insulating layer comprises an adhesive and an insulating material, wherein the insulating material is distributed in the adhesive.
[0046] In another aspect, the present invention relates to a method for preparing a laminated product as described above, said method comprising the steps of:
[0047] 1) Provide thermal insulation by:
[0048] i) mixing the thermal insulation material with the binder,
[0049] ii) applying the mixture of step i) onto a substrate surface and allowing the mixture to cure; and
[0050] iii) optionally removing the substrate;
[0051] 2) providing reinforcing fibers in the form of a continuous phase, the reinforcing fibers being arranged on each side of the thermal insulation layer obtained in step 1);
[0052] 3) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0053] (b) at least one isocyanate-reactive polyol,
[0054] (c) optionally a chain extender and / or a cross-linking agent,
[0055] (d) flame retardants,
[0056] (e) optionally a filler,
[0057] (f) a blowing agent,
[0058] (g) a catalyst, and
[0059] (h) optionally additives and / or auxiliaries,
[0060] 4) mixing the polyol component obtained in step 3) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0061] 5) spraying or injecting the mixture obtained in step 4) onto the continuous phase reinforcing fibers provided on each side of the thermal insulation layer provided in step 2) through a first nozzle or injection head, and optionally spraying the discontinuous phase reinforcing fibers onto the continuous phase reinforcing fibers provided in step 2) through a second nozzle to obtain a sprayed or injected product;
[0062] 6) hot pressing the sprayed or injected product obtained in step 5) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0063] 7) demoulding and optionally trimming to obtain a laminated product comprising a polyurethane composite material disposed on each side of the thermal insulation layer;
[0064] The polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0065] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; and
[0066] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0067] Surprisingly, it is found that in the present application, the laminated product as described above or the laminated product prepared by the method as described above shows reduced weight, good mechanical strength, good flame retardancy and excellent voltage resistance. In addition, the method is carried out in a robust and easy manner. Accordingly, the laminated product is obtained cost-effectively.
[0068] In yet another aspect, the present invention relates to a covering article comprising a laminate product as described above or a laminate product prepared by a method as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 Shown is the STM method used to prepare PU composites.
[0070] Figure 2 The LFI method for preparing PU composites is shown.
[0071] Figure 3 Shown is a covered article comprising a PU composite material and a metal sheet.
[0072] Figure 4 Shown is a laminate product comprising two PU composite layers and a thermal insulation layer in between.
[0073] Figure 5 A method for producing a thermal insulation layer is shown.
[0074] Figure 6 A method for preparing a laminated product is shown. DETAILED DESCRIPTION
[0075] Unless otherwise defined, all technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the invention belongs. As used herein, unless otherwise specified, the following terms have the meanings assigned to them below.
[0076] As used herein, the articles "a" and "an" refer to one or to more than one (ie, to at least one) of the grammatical object of the article. For example, "an element" refers to one element or more than one element.
[0077] As used herein, the expression "comprising" also encompasses the expression "consisting of".
[0078] Unless otherwise indicated, all percentages (%) refer to "percentages by weight".
[0079] Unless indicated otherwise, temperature refers to room temperature and pressure refers to ambient pressure.
[0080] As used herein, the term "reinforcement fibers in the form of a continuous phase" refers to a fiber layer in which the fibers contained in the layer are combined or connected to each other to form an integral layer.
[0081] As used herein, the term "reinforcement fibers in the form of a discontinuous phase" refers to fibers that are not connected to each other or are not in an integral form.
[0082] I.PU composite materials
[0083] In one aspect, the present invention relates to a polyurethane (PU) composite material, wherein the polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0084] The polyurethane foam is obtained from a two-component reaction system comprising the following substances:
[0085] Isocyanate component consisting of:
[0086] (a) at least one isocyanate or isocyanate prepolymer, and
[0087] The polyol component consists of:
[0088] (b) at least one isocyanate-reactive polyol,
[0089] (c) optionally a chain extender and / or a cross-linking agent,
[0090] (d) flame retardants,
[0091] (e) optionally a filler,
[0092] (f) a blowing agent,
[0093] (g) a catalyst, and
[0094] (h) optionally additives and / or auxiliaries,
[0095] wherein the reinforcing fiber is selected from glass fiber, basalt fiber, carbon fiber and natural fiber, preferably glass fiber and basalt fiber, more preferably glass fiber; and
[0096] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers.
[0097] In one embodiment, the reinforcing fibers are impregnated with polyurethane foam.
[0098] In one embodiment, the reinforcing fibers in the continuous phase form are in the form of a mat, a woven fabric, or a combination thereof. In a specific embodiment, the reinforcing fibers in the continuous phase form are assembled roving E512 commercially available from China Jushi Co. Ltd. In this application, the term "mat" means materials in the form of felt, thin cloth, relatively thin sheets, knitted shapes, etc. In one embodiment, the mat is formed by methods known in the art, such as conventional methods or electrostatic spinning methods using warp and weft yarns. On these bases, it should be understood that the reinforcing fibers in the continuous phase form can be in the form of a cover net, chopped mat, woven fabric, nonwoven fabric, fiber cloth, stitched mat, etc.
[0099] In one embodiment, the reinforcing fibers in the continuous phase have a density of 200 to 1600 g / m 2 , preferably 400 to 900 g / m 2 .
[0100] In one embodiment, the PU composite comprises 1 to 4 layers of a mat, a woven fabric or a combination thereof, preferably 1 to 4 layers of a reinforcing fiber mat in the form of a continuous phase, such as 1, 2, 3 or 4 layers.
[0101] In one embodiment, the PU composite material comprises reinforcing fibers in discontinuous form. In one embodiment, the reinforcing fibers in the discontinuous phase form have a length of 6 to 100 mm, preferably 8 to 80 mm, more preferably 10 to 50 mm, and even more preferably 12 to 25 mm. In a specific embodiment, the reinforcing fibers in the discontinuous phase form are assembled roving E440 commercially available from China Jushi Co. Ltd.
[0102] In one embodiment, the density of the PU composite is less than 2.2 g / cm 3 , preferably less than 1.8 g / cm 3 , preferably less than 1.6 g / cm 3 , more preferably less than 1.5 g / cm 3 , even more preferably less than 1.3 g / cm 3 , most preferably less than 1.2 g / cm 3 .
[0103] In one embodiment, the PU composite material is prepared in the form of a sheet having a thickness of 0.5 to 10 mm, preferably 1 to 5 mm, more preferably 1 to 3 mm, even more preferably 1 to 2 mm.
[0104] In one embodiment, the polyurethane composite material comprises a flame retardant (d) selected from the group consisting of expandable graphite, red phosphorus, ammonium polyphosphate, triethyl phosphate, tris(2-chloroisopropyl) phosphate, melamine, expandable graphite (EG), red phosphorus, ammonium polyphosphate, tris(1-chloro-2-propyl) phosphate (TCPP), triethyl phosphate (TEP), chlorine- and bromine-containing polyols such as epichlorohydrin, chlorendic anhydride and trichlorobutylene oxide (TCBO), phosphorus-containing polyols such as esters of orthophosphoric acid, esters of phosphorous acid, phosphonate polyols, phosphine oxide polyols and phosphoramide polyols.
[0105] In one embodiment, the tensile strength of the PU composite measured according to GB / T1447-2005 is at least 90 MPa, preferably at least 95 MPa, more preferably at least 100 MPa, even more preferably at least 120 MPa and most preferably at least 130 MPa.
[0106] In one embodiment, the PU composite has a flexural strength measured according to GB / T1449-2005 of at least 180 MPa, preferably at least 185 MPa, more preferably at least 190 MPa, even more preferably at least 200 MPa and most preferably at least 230 MPa.
[0107] In one embodiment, the PU composite material passes the UL94 V0 grade fire test. In one embodiment, the PU composite material passes the UL 94 5VA fire test.
[0108] Polyurethane
[0109] In the preparation of PU composite materials, an "isocyanate component" and a "polyol component" (hereinafter also referred to as a "resin component" or "resin") are used, wherein the "polyol component" is a mixture of a polyol (b) reactive to isocyanate, optionally a chain extender and / or a crosslinker (c), a flame retardant (d), optionally a filler (e), a blowing agent (f), a catalyst (g) and optionally an auxiliary agent and an additive (h), and the "isocyanate component" is at least one isocyanate or an isocyanate prepolymer (a). The polyol component reacts with the isocyanate to form a urethane bond. Such a system is disclosed, for example, in U.S. Pat. No. 4,218,543.
[0110] It is worth noting that, in the present application, the polyol component does not include reinforcing fibers, both in continuous and discontinuous forms.
[0111] In a preferred embodiment, the "isocyanate component" and the "polyol component" are impact mixed and sprayed or injected into the mold at about atmospheric pressure, and then the mold is closed. The mold is preheated at 40 to 180° C., preferably 70 to 150° C., more preferably 90 to 130° C., and an insert (such as a metal sheet, a metal foil or a solid flame retardant layer) is optionally arranged on the mold surface. The raw materials are uniformly sprayed or injected on the fiber fabric in the mold, and then the molded part is demolded after a time of generally 1 to 15 minutes, preferably 90 seconds to 10 minutes, more preferably 2 to 8 minutes.
[0112] Isocyanate or isocyanate prepolymer (a)
[0113] The isocyanate component used to prepare the polyurethane of the present invention includes any isocyanate known for preparing polyurethanes. These include aliphatic, alicyclic, araliphatic and / or aromatic isocyanates, such as tri-, tetra-, penta-, hexa-, hepta- and / or octamethylene diisocyanate, 2-methylpentamethylene 1,5-diisocyanate, 2-ethylbutylene 1,4-diisocyanate, pentamethylene 1,5-diisocyanate, butylene 1,4-diisocyanate, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate, IPDI), 1,4- and / or 1,3-bis(isocyanatomethyl)cyclohexane (HXDI), cyclo ... 1,5-diisocyanate, 1,4-diisocyanate, 1,4-diisocyanate, 1,4-diisocyanate, 1,4-diisocyanate, 1,3-diisocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate, IPDI), 1,4- and / or 1,3-bis(isocyanatomethyl)cyclohexane (HXDI), cyclopentamethylene 1,5-diisocyanate, 1,4-diiso Hexane 1,4-diisocyanate, 1-methylcyclohexane 2,4- and / or 2,6-diisocyanate and / or dicyclohexylmethane 4,4'- / 2,4'- and 2,2'-diisocyanate, diphenylmethane 2,2'-, 2,4'- and / or 4,4'-diisocyanate (MDI), polymeric MDI, naphthylene 1,5-diisocyanate (NDI), toluene 2,4- and / or 2,6-diisocyanate (TDI), 3,3'-dimethyldiphenyl diisocyanate, 1,2-diphenylethane diisocyanate and / or phenylene diisocyanate. Particular preference is given to using 2,2'-, 2,4'- and / or 4,4'-diisocyanates and polymeric MDI.
[0114] Further possible isocyanates are given, for example, in “Kunststoffhandbuch, Band 7, Polyurethane” [Plastics handbook, Volume 7, Polyurethanes], Carl Hanser Verlag, 3rd edition, 1993, Chapters 3.2 and 3.3.2.
[0115] In addition, the isocyanate component can also be used in the form of an isocyanate prepolymer. The isocyanate prepolymer can be obtained by reacting the above-mentioned isocyanates with a further polyol (a'), for example at a temperature of 30-100° C., preferably about 80° C. 4,4'-MDI is preferably used together with uretonimine-modified MDI and commercially available polyols based on polyesters (e.g. polyesters derived from adipic acid) or polyethers (e.g. polyethers derived from ethylene oxide and / or propylene oxide) for the preparation of the prepolymers used according to the invention. 4,4'-MDI and polyols derived from ethylene oxide and / or propylene oxide are preferably used for the preparation of the prepolymers used according to the invention.
[0116] Further polyols (a′) are known to the person skilled in the art and are described, for example, in “Kunststoffhandbuch [Plastics handbook], Volume 7, Polyurethane [Polyurethanes]”, Carl Hanser Verlag, 3rd edition, 1993, Chapter 3.1.
[0117] Ether-based prepolymers are preferably obtained by reacting isocyanates, particularly preferably 4,4'-MDI, with 2- to 3-functional polyoxypropylene polyols and / or polyoxypropylene-polyoxyethylene polyols. They are usually prepared by the generally known base-catalyzed addition of propylene oxide alone or in a mixture with ethylene oxide onto H-functional, in particular OH-functional, starter substances. The starter substances used are, for example, water, ethylene glycol or propylene glycol and glycerol or trimethylolpropane. In addition, multimetal cyanide compounds, known as DMC catalysts, can also be used as catalysts. For example, the polyethers described below under component (b) can be used as additional polyols (a').
[0118] When ethylene oxide / propylene oxide mixtures are used, ethylene oxide is preferably used in an amount of 10 to 50% by weight, based on the total amount of alkylene oxides. The alkylene oxides can be incorporated in blocks or as a random mixture. Particular preference is given to introducing ethylene oxide end blocks ("EO endblocks") in order to increase the content of more reactive primary OH end groups. The number-average molecular weight of the polyol (a') is preferably in the range from 1750 to 5500 g / mol.
[0119] If appropriate, conventional chain extenders or crosslinkers are added to the further polyols mentioned in the preparation of the isocyanate prepolymer. Conventional chain extenders or crosslinkers may be the same as those described in c) below. Particular preference is given to using dipropylene glycol, tripropylene glycol or monoethylene glycol (MEG) as chain extenders or crosslinkers.
[0120] Isocyanate-reactive polyol (b)
[0121] The isocyanate-reactive polyol (b) may be any polyol that is useful in the art for polyurethane preparation and has at least two reactive hydrogen atoms. For example, polyether polyamines and / or polyols selected from polyether polyols and polyester polyols, or mixtures thereof may be used.
[0122] The polyols preferably used are polyether polyols having a weight average molecular weight of 200 to 10000, preferably 300 to 8000, more preferably 500 to 6000, most preferably 2500 to 3500, and an OH value of 20 to 1200 mg KOH / g, preferably 30 to 1000 mg KOH / g, more preferably 40 to 500 mg KOH / g; and / or polyester polyols having a molecular weight of 350 to 2000, preferably 350 to 650, and an OH value of 60 to 650 mg KOH / g, preferably 120 to 310 mg KOH / g. The following polyols are preferred in the present invention: 2095(BASF), 2090(BASF)、LUPRANOL 3505 / 1(BASF)、 3905(BASF), 3907(BASF), 3909(BASF), PS 3152, PS2412, PS1752, CF 6925 (Stepan Company).
[0123] The polyether polyols used in the present invention can be prepared by known methods. For example, they can be prepared from one or more alkylene oxides having 2 to 4 carbon atoms in the alkylene group by anionic polymerization, using alkali metal hydroxides such as sodium hydroxide or potassium hydroxide, or using alkali metal alcoholates such as sodium methoxide, sodium ethoxide or potassium ethoxide or potassium propoxide as catalysts, adding at least one initiator molecule containing 2 to 8 reactive hydrogen atoms; or by cationic polymerization, using Lewis acids such as antimony pentachloride, boron fluoride etherate, etc., or bleaching earth as catalysts.
[0124] Examples of suitable alkylene oxides are tetrahydrofuran, 1,2-propylene oxide, 1,2-butylene oxide or 2,3-butylene oxide, styrene oxide and preferably ethylene oxide and 1,2-propylene oxide. The alkylene oxides can be used individually, in alternating succession or as a mixture.
[0125] Examples of starter molecules which can be used are: water, organic dicarboxylic acids such as succinic acid, adipic acid, phthalic acid and terephthalic acid, aliphatic and aromatic, optionally N-mono-, N,N- and N,N′-dialkyl-substituted diamines having 1 to 4 carbon atoms in the alkyl radical, for example optionally mono- and dialkyl-substituted ethylenediamine, diethylenetriamine, triethylenetetramine, 1,3-propylenediamine, 1,3- or 1,4-butylenediamine, 1,2-, 1,3-, 1,4-, 1,5- and 1,6-hexamethylenediamine, phenylenediamine, 2,3-, 2,4- and 2,6-tolylenediamine and 4,4′-, 2,4′- and 2,2′-diaminodiphenylmethane.
[0126] Polyester polyols can be prepared, for example, from dicarboxylic acids having 2 to 12 carbon atoms, preferably 4 to 6 carbon atoms, and polyols. Examples of dicarboxylic acids that can be used are: aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid and sebacic acid, and aromatic dicarboxylic acids such as phthalic acid, isophthalic acid and terephthalic acid. The dicarboxylic acids can be used alone or in the form of a mixture, for example in the form of a mixture of succinic acid, glutaric acid and adipic acid. Examples of polyols are diols having 2 to 10, preferably 2 to 6, carbon atoms, such as ethylene glycol, diethylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 2,2-dimethyl-1,3-propanediol, 1,3-propanediol and dipropylene glycol, triols having 3 to 6 carbon atoms, such as glycerol and trimethylolpropane, and pentaerythritol as a higher-functionality alcohol. Depending on the desired properties, the polyols can be used alone or optionally mixed with one another.
[0127] The amount of polyether polyols and / or polyester polyols is preferably 0 to 40% by weight, particularly preferably 15 to 35% by weight, based on the total weight of the resin.
[0128] Chain extender and / or crosslinker (c)
[0129] Chain extenders and / or crosslinkers (c) which can be used are substances having a molar mass of preferably less than 500 g / mol, particularly preferably from 60 to 400 g / mol, wherein chain extenders have 2 hydrogen atoms reactive toward isocyanates and crosslinkers have 3 hydrogen atoms reactive toward isocyanates. These substances can be used individually or preferably in the form of a mixture. Preference is given to using diols and / or triols having a molecular weight of less than 500, particularly from 60 to 400, in particular from 60 to 350. Examples of those that can be used are aliphatic, cycloaliphatic and / or araliphatic diols having 2 to 14, preferably 2 to 10, carbon atoms, such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol, 1,2-, 1,3- and 1,4-dihydroxycyclohexane, diethylene glycol, dipropylene glycol, tripropylene glycol, diethanolamine or triols, such as 1,2,4- or 1,3,5-trihydroxycyclohexane, glycerol and trimethylolpropane. Chain extenders and / or crosslinkers (c) are preferably selected from ethylene glycol, diethylene glycol, dipropylene glycol, tripropylene glycol and glycerol.
[0130] The amount of chain extenders and / or crosslinkers c) (if present) is preferably 0 to 50% by weight, particularly preferably 10 to 40% by weight, based on the total weight of the resin.
[0131] Flame retardant (d)
[0132] The flame retardant (d) that can be used is an additive flame retardant and a reactive flame retardant, or a combination thereof. An additive flame retardant is a monomer molecule that is not chemically bonded to a polymer. An additive flame retardant can be in the form of a solid flame retardant, a liquid flame retardant, or a combination thereof. Commercial additive flame retardants are tris(2-chloroisopropyl) phosphate, melamine, expandable graphite (EG), red phosphorus, ammonium polyphosphate, tris(1-chloro-2-propyl) phosphate (TCPP), triethyl phosphate (TEP). Reactive flame retardants are generally polyols containing halogens and / or phosphorus. Flame retardant polyols have terminal hydroxyl groups that can react with polyisocyanates in PU synthesis. Halogen-containing FR polyols can be chlorine- and bromine-containing polyols, such as epichlorohydrin, chlorendic anhydride, and trichlorobutylene oxide (TCBO); phosphorus-containing polyols, such as orthophosphates, phosphites, phosphonate polyols, phosphine oxide polyols, and phosphoramidite polyols.
[0133] For the purpose of flame retardancy, the total amount of the flame retardant is preferably 5 to 30% by weight, more preferably 10 to 25% by weight, based on the total weight of the resin.
[0134] Filler(e)
[0135] Fillers that can be used are customary organic or inorganic fillers known per se. Individual examples that may be mentioned are: inorganic fillers such as silicate minerals, metal oxides such as aluminum oxide, titanium oxide and iron oxide. In the present application, the average particle size of the filler is less than 600 μm, preferably less than 500 μm, more preferably less than 400 μm. Filler (e) is preferably selected from titanium oxide and iron oxide.
[0136] The amount of filler is 0 to 30% by weight, preferably 0 to 15% by weight, based on the total weight of the resin. The weight ratio of flame retardant (d) to filler (e) is 0.1 to 10, preferably 0.5 to 2.
[0137] Fillers can be used to reduce the coefficient of thermal expansion of the polyurethane foam, which is greater than that of metal, for example, and thus match it to that of the metal. This is particularly advantageous for a durable, strong bond between the metal sheet and the polyurethane core layer, since this results in lower stresses between the layers when they are subjected to thermal loads.
[0138] In the present application, filler (e) does not include reinforcing fibers, ie, reinforcing fibers in continuous form and in discontinuous form. In other words, the polyol component does not include reinforcing fibers, ie, reinforcing fibers in continuous form and in discontinuous form.
[0139] Foaming agent (f)
[0140] The blowing agent (f) used according to the present invention preferably comprises water. The blowing agent (f) used may also comprise other chemical and / or physical blowing agents and water in the art. Chemical blowing agents are compounds that form gaseous products by reacting with isocyanates, examples being water or formic acid. Physical blowing agents are compounds that have been dissolved or emulsified in the starting materials for polyurethane preparation and evaporate under the conditions of polyurethane formation. For example, these substances are hydrocarbons, halogenated hydrocarbons and other compounds, such as perfluoroalkanes, such as perfluorohexane, fluorochlorocarbons, and ethers, esters, ketones and / or acetals. In a preferred embodiment, water is used as the only blowing agent (f). In this case, the polyurethane foam according to the present invention is a water-blown polyurethane spray foam. Regarding water, there are no particular restrictions. Mineral water, deionized water or tap water can be used.
[0141] The amount of the blowing agent is 0 to 5% by weight, preferably 0.1 to 3% by weight, based on the total weight of the resin.
[0142] Catalyst(g)
[0143] As catalyst (g), any compound that accelerates the isocyanate-polyol reaction can be used. Such compounds are known and described, for example, in "Kunststoffhandbuch, Vol. 7, Polyurethane", Carl Hanser Verlag, 3rd edition, 1993, Chapter 3.4.1. These substances include amine-based catalysts and catalysts based on organometallic compounds.
[0144] As catalysts based on organometallic compounds, for example, organotin compounds such as tin(II) salts of organic carboxylic acids, for example tin(II) acetate, tin(II) octoate, tin(II) ethylhexanoate and tin(II) laurate, and dialkyltin(IV) salts of organic carboxylic acids, for example dibutyltin diacetate, dibutyltin dilaurate, dibutyltin maleate and dioctyltin diacetate, and bismuth carboxylates, for example bismuth(III) neodecanoate, bismuth 2-ethylhexanoate and bismuth octoate, or alkali metal salts of carboxylic acids, for example potassium acetate or potassium formate, can be used.
[0145] Preference is given to using amine-based catalysts as catalyst (g), such as N,N,N',N'-tetramethyldipropylenetriamine, 2-[2-(dimethylamino)ethyl-methylamino]ethanol, N,N,N'-trimethyl-N'-2-hydroxyethyl-bis-(aminoethyl) ether, bis(2-dimethylaminoethyl) ether, N,N,N,N,N-pentamethyldiethylenetriamine, N,N,N-triethylaminoethoxyethanol, dimethylcyclohexylamine, trimethylhydroxyethylethylenediamine, dimethylbenzylamine, triethylamine, triethylenediamine, pentamethyldipropylenetriamine, dimethylethanolamine, N-methylimidazole, N-ethylimidazole, tetramethylhexamethylenediamine, tris(dimethylaminopropyl)hexahydrotriazine, dimethylaminopropylamine, N-ethylmorpholine, diazabicycloundecene and diazabicyclononene. Examples that may be mentioned here are Jeffcat ZF10 (CAS No. 83016-70-0), Jeffcat DMEA (CAS No. 108-01-0) and Dabco T (CAS No. 2212-32-0). Such reactive catalysts have the effect of reducing VOC values.
[0146] The amount of catalyst (g) is preferably 0.1 to 5% by weight, particularly preferably 0.1 to 3.5% by weight, based on the total weight of the resin.
[0147] Additives and / or auxiliary agents (h)
[0148] The additives and / or auxiliary agents (h) that can be used include, but are not limited to, surfactants, preservatives, colorants, antioxidants, reinforcing agents, stabilizers and water absorbents. When preparing polyurethane foams, it is generally highly preferred to use a small amount of surfactant to stabilize the foaming reaction mixture until it solidifies. Such surfactants advantageously include liquid or solid organosiloxane surfactants in an amount sufficient to stabilize the foaming reaction mixture. Typically, the amount of auxiliary agents, especially surfactants, is preferably 0 to 15% by weight, more preferably 0.5 to 6% by weight, based on the total weight of the resin.
[0149] Further information on the use and mode of action of the abovementioned auxiliaries and additives as well as further examples is given, for example, in "Kunststoffhandbuch, Band 7, Polyurethane" ["Plastics handbook, Volume 7, Polyurethanes"], Carl Hanser Verlag, 3rd edition, 1993, Chapter 3.4.
[0150] The weight ratio of the polyol component to the isocyanate component is 1:0.6 to 1:2, preferably 1:0.7 to 1:1.
[0151] Method for preparing PU composite material
[0152] In another aspect, the present invention relates to a method for preparing a PU composite material as described above, wherein the method comprises the following steps:
[0153] 1) providing reinforcing fibers in the form of a continuous phase;
[0154] 2) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0155] (b) at least one isocyanate-reactive polyol,
[0156] (c) optionally a chain extender and / or a cross-linking agent,
[0157] (d) flame retardants,
[0158] (e) optionally a filler,
[0159] (f) a blowing agent,
[0160] (g) a catalyst, and
[0161] (h) optionally additives and / or auxiliaries,
[0162] 3) mixing the polyol component obtained in step 2) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0163] 4) spraying or injecting the mixture obtained in step 3) onto the reinforcing fibers in the continuous phase provided in step 1) through a first nozzle or an injection head, and optionally spraying the reinforcing fibers in the discontinuous phase onto the reinforcing fibers in the continuous phase provided in step 1) through a second nozzle to obtain a sprayed or injected product;
[0164] 5) hot pressing the sprayed or injected product obtained in step 4) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0165] 6) demoulding and optional trimming;
[0166] wherein the polyurethane composite material obtained in step 6) comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material, and
[0167] The reinforcing fibers comprise 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers;
[0168] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0169] In one embodiment, the weight ratio of the total amount of reinforcing fibers in the continuous phase form and the optional reinforcing fibers in the discontinuous phase form used in steps 1), 3) and 4) to the total amount of the polyol component and the isocyanate component used in step 3) is about (35-75):(25-65).
[0170] In one embodiment, the reinforcing fibers in the discontinuous phase form in step 3) are obtained by in-situ chopping long fibers and added to a mixture of an isocyanate component and a polyol component of the polyurethane at a constant rate, and the length of the chopped reinforcing fibers is 6 to 100 mm, preferably 8 to 80 mm, more preferably 10 to 50 mm, and even more preferably 12 to 25 mm.
[0171] In one embodiment, the reinforcing fibers in the continuous phase in step 1) are in the form of a mat, a woven fabric, or a combination thereof.
[0172] Spray Transfer Molding (STM) Method
[0173] In one aspect, the present invention provides a spray transfer molding (STM) method for preparing the PU composite material as described above, comprising the following steps:
[0174] 1) providing reinforcing fibers in the form of a continuous phase;
[0175] 2) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0176] (b) at least one isocyanate-reactive polyol,
[0177] (c) optionally a chain extender and / or a cross-linking agent,
[0178] (d) flame retardants,
[0179] (e) optionally a filler,
[0180] (f) a blowing agent,
[0181] (g) a catalyst, and
[0182] (h) optionally additives and / or auxiliaries,
[0183] 3) mixing the polyol component obtained in step 2) with the isocyanate component at a temperature of 20 to 80° C. to obtain a mixture;
[0184] 4) spraying the mixture obtained in step 3) onto the reinforcing fibers in the continuous phase provided in step 1) through a first nozzle, and optionally spraying the reinforcing fibers in the discontinuous phase onto the reinforcing fibers in the continuous phase provided in step 1) through a second nozzle to obtain a sprayed product;
[0185] 5) hot pressing the sprayed product obtained in step 4) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0186] 6) demoulding and optional trimming;
[0187] The polyurethane composite material obtained in step 6) comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material,
[0188] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; and
[0189] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0190] In one embodiment, the method comprises, in step 1), providing from 1 to 4 layers of reinforcing fibers in the form of a continuous phase, such as 1, 2, 3 or 4 layers.
[0191] In one embodiment, in step 1), the open mold is preheated at a temperature of 40 to 180°C, preferably 70 to 150°C, more preferably 90 to 130°C.
[0192] In one embodiment, in step 4), the mixture obtained in step 3) is sprayed onto the reinforcing fiber layer using a first nozzle. In one embodiment, in step 4), the first nozzle moves at a speed such that the resulting PU composite material is relatively thin, for example, with a thickness of 0.5 to 10 mm, preferably 1 to 5 mm, more preferably 1 to 3 mm, even more preferably 1 to 2 mm.
[0193] In one embodiment, in step 4), the mixture is sprayed by continuously transferring from one edge to another edge on both surfaces of the reinforcing fiber layer with the first nozzle. In this embodiment, spraying can be carried out on the first surface of the reinforcing fiber layer, and then the PU with the reinforcing fiber layer is continuously picked up, turned over and laid, and then sprayed on the second surface of the reinforcing fiber layer.
[0194] In another embodiment, in step 4), spraying the mixture is performed on one surface of the reinforcing fiber layer.
[0195] In a preferred embodiment, the method includes spraying the reinforcing fibers of the discontinuous phase form onto the reinforcing fiber layer using the second nozzle in step 4). In this embodiment, the reinforcing fibers of the discontinuous phase form can be sprayed on the entire region or partial region of the target composite material as required. In this embodiment, the discontinuous reinforcing fibers are sprayed while spraying the mixture obtained in step 3). Therefore, the discontinuous reinforcing fibers can be arranged and distributed in the mixture obtained in step 3).
[0196] In one embodiment, the weight ratio of the total amount of reinforcing fibers in the continuous phase form and optionally the discontinuous phase form used in steps 1) and 4) to the total amount of the polyol component and the isocyanate component used in step 3) is about (35-75):(25-65).
[0197] In one specific embodiment, the reinforcing fibers comprise 100 weight percent of the reinforcing fibers in the continuous phase, based on the total weight of the reinforcing fibers.
[0198] In one embodiment, in step 5), the mold is closed and maintained for 1 to 15 minutes, preferably 90 seconds to 10 minutes, more preferably 2 to 8 minutes.
[0199] In one embodiment, in step 5), the mold is closed and maintained at a temperature of 40 to 180° C., preferably 70 to 150° C., more preferably 90 to 130° C. In one embodiment, in step 5), the mold is closed and maintained under a hot press clamping force of 100 to 2000 tons, preferably 200 to 1500 tons, more preferably 300 to 1000 tons.
[0200] In one embodiment, the PU composite material can be optionally prepared to contain at least one insert such as a metal sheet, a metal foil or a solid flame retardant layer. In one embodiment, a covered article comprising a PU composite material and at least one metal sheet is obtained. In another embodiment, a covered article comprising a PU composite material and a solid flame retardant layer is obtained.
[0201] In one embodiment, in step 6), the trimming step is carried out while demoulding, and a tool for cutting the trimming in the STM method is designed on the mold. In this embodiment, the device used in the STM method is designed to have a tool for cutting the trimming on the mold.
[0202] Long Fiber Injection (LFI) Method
[0203] In another aspect, the present invention also provides a long fiber injection (LFI) method for preparing the PU composite material as described above, comprising the following steps:
[0204] 1) providing reinforcing fibers in the form of a continuous phase;
[0205] 2) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0206] (b) at least one isocyanate-reactive polyol,
[0207] (c) optionally a chain extender and / or a cross-linking agent,
[0208] (d) flame retardants,
[0209] (e) optionally a filler,
[0210] (f) a blowing agent,
[0211] (g) a catalyst, and
[0212] (h) optionally additives and / or auxiliaries,
[0213] 3) mixing the polyol component obtained in step 2) with the isocyanate component and the reinforcing fiber in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0214] 4) injecting the mixture obtained in step 3) onto the reinforcing fibers in the form of a continuous phase provided in step 1) through an injection head to obtain an injected product;
[0215] 5) hot pressing the injected product obtained in step 4) in a mold at a temperature of 40 to 180° C. and under a hot pressing clamping force of 100 to 2000 tons; and
[0216] 6) demoulding and optional trimming;
[0217] The polyurethane composite material obtained in step 6) comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material,
[0218] The reinforcing fibers contain 75 to <100 wt % of reinforcing fibers in the form of a continuous phase and >0 to 25 wt % of reinforcing fibers in the form of a discontinuous phase, based on the total weight of the reinforcing fibers;
[0219] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0220] In one embodiment, the method comprises, in step 1), providing from 1 to 4 layers of reinforcing fibers in the form of a continuous phase, such as 1, 2, 3 or 4 layers.
[0221] In one embodiment, in step 1), the open mold is preheated at a temperature of 40 to 180°C, preferably 70 to 150°C, more preferably 90 to 130°C.
[0222] In one embodiment, in step 3), mixing is performed in a mixing chamber immediately prior to injection.
[0223] In one embodiment, in step 3), the reinforcing fibers in the form of a discontinuous phase are obtained by in-situ chopping of long fibers, followed by entering a mixing chamber, and added to the mixture of the isocyanate component and the polyol component (i.e., added to the mixing chamber) at a constant rate. In this embodiment, the reinforcing fibers before chopping are in the form of fiber coils, which are wound on a bobbin.
[0224] In one embodiment, the reinforcing fibers are added at a rate such that the resulting PU composition has a fiber content of 35 to 75 wt. % reinforcing fibers, based on the total weight of the PU composite.
[0225] In one embodiment, the weight ratio of the total amount of the continuous phase reinforcing fibers and the discontinuous phase reinforcing fibers used in steps 1) and 3) to the total amount of the polyol component and the isocyanate component used in step 3) is about (35-75):(25-65).
[0226] In one embodiment, in step 3), the length of the reinforcing fibers in the discontinuous phase is 6 to 100 mm, preferably 8 to 80 mm, more preferably 10 to 50 mm, even more preferably 12 to 25 mm.
[0227] In one embodiment, in step 4), the mixture obtained in step 3) is injected onto the surface of the reinforcing fiber layer in the open mold using an injection head.
[0228] In one embodiment, in step 5), the mold is closed and maintained at a temperature of 40 to 180° C., preferably 70 to 150° C., more preferably 90 to 130° C. In one embodiment, in step 5), the mold is closed and maintained under a hot press clamping force of 100 to 2000 tons, preferably 200 to 1500 tons, more preferably 300 to 1000 tons. In one embodiment, in step 5), the mold is closed and maintained for 1 to 15 minutes, preferably 90 seconds to 10 minutes, more preferably 2 to 8 minutes.
[0229] In one embodiment, the PU composite material can be optionally prepared to contain at least one insert such as a metal sheet, a metal foil or a solid flame retardant layer. In one embodiment, a covered article comprising a PU composite material and at least one metal sheet is obtained. In another embodiment, a covered article comprising a PU composite material and at least one metal foil is obtained.
[0230] In one embodiment, in step 6), a trimming step is performed while demolding, wherein a tool for cutting the trimming in the LFI process is designed on the mold. In this embodiment, the apparatus used in the LFI process is designed to have a tool for cutting the trimming on the mold.
[0231] Surprisingly, the inventors have found that all of the above methods allow the preparation of films having a thickness of 0.5 to 10 mm, preferably 1 to 5 mm, more preferably 1 to 3 mm, even more preferably 1 to 2 mm and a reduced density, for example less than 1.8 g / cm 3 , preferably less than 1.6g / cm 3 , more preferably less than 1.5 g / cm 3 , even more preferably less than 1.3 g / cm 3 , most preferably less than 1.2g / cm 3 In addition, they have the advantages of less requirements on raw materials, good impregnation between fiber and PU, low cost and short cycle.
[0232] Furthermore, the relatively low pressure and temperature requirements of the STM and LFI methods translate into lower tooling costs. In addition, STM and LFI can successfully mold complex parts with high-resolution features, containing both thick and thin walls.
[0233] Covering products
[0234] In one aspect, the present invention provides a covering article comprising at least one layer of a polyurethane composite material as described above or a polyurethane composite material obtained by a method as described above.
[0235] In one embodiment, the thickness of the covered article is from 1 to 5 mm, preferably from 1.2 to 3 mm.
[0236] In one embodiment, the covering product further comprises at least one metal sheet located on at least one side of at least one PU composite sheet. In a preferred embodiment, the covering product comprises two metal sheets located on both sides of the PU composite sheet. In this embodiment, the covering product contains a PU composite sheet as a core layer and two metal sheets located on both sides of the core layer, forming a sandwich structure. In another preferred embodiment, the covering product comprises a metal sheet located on one side of the PU composite sheet. In some alternative embodiments, the covering product comprises a metal sheet and two PU composite sheets located on both sides of the metal sheet. In one embodiment, the metal sheets are independently selected from aluminum alloys, iron, steel and aluminum sheets.
[0237] The thickness of the metal sheet may be 0.08 to 1.2 mm, preferably 0.08 to 0.6 mm, more preferably 0.12 to 0.4 mm and most preferably 0.2 to 0.3 mm.
[0238] In a preferred embodiment, the thickness of the metal sheet is 0.2 to 1.2 mm, preferably 0.5 to 1.0 mm. It has been found that a metal sheet of such thickness advantageously provides improved mechanical strength, which enables the covered article having such a metal sheet to further meet mechanical strength requirements.
[0239] The covering product according to the present invention can be used as an upper cover of a battery pack.
[0240] The covering product according to the present invention has good fire resistance, good electromagnetic interface (EMI) shielding performance, excellent electrical insulation and excellent voltage resistance, and is suitable for use as the upper cover of the battery pack. In addition, the covering product according to the present invention passed the UL94 V0 level fire test at a thickness of 2 mm. The battery pack containing the covering product according to the present invention as the upper cover passed the external combustion test according to GB 38031-2020.
[0241] The covering article according to the present invention also has good shielding efficiency (SE). In one embodiment, the covering article shows a shielding ratio (dB) of at least 40, preferably at least 50, and more preferably at least 60. The dB value is calculated by the formula [dB] = 20 × log (E0 / E1), where E0 represents the field strength without the covering article and E1 represents the field strength with the covering article. For example, a dB value of 60 indicates that the covering article reflects and / or absorbs 99.9% of the electromagnetic energy.
[0242] II. Laminated Products
[0243] In one aspect, the invention relates to a laminate product comprising at least one thermal insulation layer and at least two layers of a polyurethane composite material, the polyurethane composite material being arranged on each side of the thermal insulation layer,
[0244] The thermal insulation layer comprises an adhesive and a thermal insulation material, wherein the thermal insulation material is distributed in the adhesive.
[0245] like Figure 4 As shown, the laminated product includes two PU composite layers and a thermal insulation layer placed between the two PU composite layers.
[0246] It should be noted that, unless otherwise specified, the PU composite material contained in the laminated product has the same meaning as the PU composite material described above in the "PU composite material" section or prepared according to the "Method for Preparing PU Composite Material" section (see Section I, PU Composite Material). For the sake of brevity, it will not be repeated here.
[0247] In one embodiment, the thermal insulation layer comprises 10 wt % to 70 wt %, preferably 20 wt % to 50 wt %, more preferably 20 wt % to 40 wt % of the thermal insulation material, based on the total weight of the thermal insulation layer. Alternatively, the surface density of the thermal insulation layer is 50-500 g / m 2 , 50-200g / m 2 100-200g / m 2 It should be understood that surface density refers to the mass (g) of material per square meter. When the weight percentage / surface density of the thermal insulation material is too high, the thermal insulation material is not easy to combine together and form a film; on the other hand, when the weight percentage / surface density of the thermal insulation material is too low, the corresponding thermal insulation performance cannot be achieved.
[0248] In one embodiment, the thermal insulation layer is an intumescent thermal insulation layer and the thermal insulation material is an intumescent thermal insulation material.
[0249] When exposed to high temperatures, intumescent insulation materials release non-combustible gases (such as SO2, CO2, ammonia, etc.) and / or water vapor, which then expand to form a carbon foam layer. The released non-combustible gases and / or water vapor dilute the surrounding oxygen density, thereby reducing the risk of fire. In addition, the formed carbon foam layer has good thermal insulation properties due to its loose structure, which can prevent high temperatures from spreading to the surroundings, thereby acting as a good thermal insulation barrier.
[0250] Suitable intumescent insulation materials include, but are not limited to, phosphorus-containing materials, nitrogen-containing materials, sulfur-containing materials, boron-containing materials, water vapor-releasing compounds such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, expandable graphite (EG), pentaerythritol, kaolin, or combinations thereof.
[0251] For example, phosphorus-containing materials include phosphates such as sodium phosphate, potassium phosphate or ammonium phosphate, ammonium polyphosphate (APP), monoammonium phosphate, diammonium phosphate, trichloroethyl phosphate (TCEP), trichloropropyl phosphate (TCPP), ammonium pyrophosphate, triphenyl phosphate, etc. Nitrogen-containing materials include melamine, melamine salts, phosphates, guanidine, melamine cyanurate, melamine formaldehyde, methylated melamine, hexamethoxymethyl melamine, urea, dimethyl urea, melamine pyrophosphate, dicyandiamide, guanyl phosphate urea and glycine. Sulfur-containing materials include sulfonates such as sodium sulfonate, potassium sulfonate or ammonium sulfonate, p-toluene sulfonate; and also include sulfates such as sodium sulfate, potassium sulfate or ammonium sulfate. Boron-containing materials include boric acid and borates such as ammonium pentaborate, zinc borate, sodium borate, lithium borate, aluminum borate, magnesium borate and borosilicate. Compounds that release water vapor by decomposition during heat exposure include, but are not limited to, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, or expandable graphite (EG). Other suitable intumescent insulation materials include multifunctional alcohols such as pentaerythritol, kaolin, and the like.
[0252] In one embodiment, the average particle size of the expandable graphite is 50 μm to 500 μm, preferably 50 μm to 300 μm, and more preferably 100 μm to 200 μm. The inventors have found that when the particle size is greater than 500 μm, it is not easy to process. On the other hand, when the particle size is less than 50 μm, the expansion ratio is limited, thereby also impairing the thermal insulation performance.
[0253] In one embodiment, the binder is selected from polyurethane, epoxy, polyethylene, polypropylene, polystyrene, or combinations thereof.
[0254] In a preferred embodiment, the adhesive is a polyurethane. As described in Section 1 (PU composites), the polyurethane is the reaction product of a reaction mixture comprising an isocyanate and a polyol reactive to isocyanate. The isocyanate and the polyol reactive to isocyanate are the same as the "isocyanate component" and "polyol reactive to isocyanate" described in Section 1 (PU composites). For the sake of brevity, this is not repeated here.
[0255] In one embodiment, the preferred polyol has a weight average molecular weight of 1000 to 10000, preferably 4000 to 6000. Preferably, the functionality of the polyol is 2 to 3. The inventors have found that the laminated product prepared by using the polyurethane material defined above is elastic and non-rigid.
[0256] In one embodiment, the expansion rate of the laminated product is 5 to 20. In other words, the laminated product can expand and expand into a product that is five to twenty times thicker than the original product. Preferably, the laminated product is less than 5 mm thick before expansion and less than 25 mm thick at its maximum after expansion. This property is particularly advantageous when the laminated product is used as a housing for a battery system. Since the inner cavity space of a battery system is generally limited, it is desirable that the expanded laminated product should not be too thick. Therefore, with the above-mentioned preferred weight percentage and surface density of the insulating material, the thickness of the expanded laminated product is not more than 25 mm, which will not damage the battery components contained in the battery system.
[0257] The expansion ratio is defined as the value calculated by dividing the thickness of the laminated product after expansion by the thickness before expansion.
[0258] In one embodiment, the laminated product further comprises at least one substrate layer disposed between the thermal insulation layer and the polyurethane composite material layer, wherein the substrate layer comprises a fiber sheet, a plastic sheet and a metal sheet.
[0259] The fiber sheet is made of, for example, glass fibers (GF), carbon fibers, natural fibers (such as bamboo fibers), and in particular, natural fibers in the form of woven fabrics or non-woven fabrics; the metal sheet is made of, for example, aluminum alloy, iron, steel, or aluminum; and
[0260] The plastic sheet is made of, for example, polyethylene (PE), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polypropylene (PP), polyurethane (PU), polyamide (PA), polyvinyl butyral (PVB), or ethylene vinyl acetate (EVA).
[0261] In one embodiment, the laminated product further comprises at least one metal sheet on a side of the laminated product. When the laminated product is applied to a battery pack, the metal sheet is arranged on a side away from the battery cells. The metal sheet mainly further improves the mechanical strength of the laminated product.
[0262] The preparation process of the thermal insulation layer is as follows Figure 5 In some specific embodiments, the thermal insulation layer is prepared by the following method:
[0263] i) mixing the thermal insulation material with the adhesive;
[0264] ii) applying the mixture obtained in step i) onto the surface of the substrate (for example by spraying or knife coating) and curing the mixture; and
[0265] iii) optionally removing the substrate to obtain the thermal insulation layer.
[0266] In a specific embodiment where the binder is polyurethane, the thermal insulation layer is prepared by:
[0267] i) mixing a thermal insulation material with a polyol component;
[0268] ii) mixing the mixture obtained in step i) with an isocyanate component;
[0269] iii) applying the mixture obtained in step ii) onto the surface of the substrate (for example by spraying or knife coating) and curing the mixture; and
[0270] iv) optionally removing the substrate to obtain the thermal insulation layer.
[0271] It should be noted that the substrate used in the above preparation method includes release paper, fiber sheet, plastic sheet and metal sheet. When the substrate is release paper, the release paper is removed from the final thermal insulation layer.
[0272] In one embodiment, the laminate product passes the UL94 V0 rating fire test. In one embodiment, the laminate product passes the UL 94 5VA fire test.
[0273] In one embodiment, the laminate product is subjected to a fire test for 10 minutes at 800-1300°C (referred to as T1) on one side. The results show that the temperature on the opposite side (referred to as T2) is less than 400°C. In a preferred embodiment, T2 is less than 350°C. In a more preferred embodiment, T2 is less than 300°C. In an even more preferred embodiment, T2 is less than 280°C. In a most preferred embodiment, T2 is less than 260°C.
[0274] Method for preparing a laminated product
[0275] In another aspect, the present invention relates to a method for preparing a laminated product as described above, said method comprising the steps of:
[0276] 1) Provide thermal insulation by:
[0277] i) mixing the thermal insulation material with the binder,
[0278] ii) applying the mixture of step i) onto the substrate surface (for example by spraying or knife coating) and allowing the mixture to cure; and
[0279] iii) optionally removing the substrate;
[0280] 2) providing reinforcing fibers in the form of a continuous phase, the reinforcing fibers being arranged on each side of the thermal insulation layer obtained in step 1);
[0281] 3) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0282] (b) at least one isocyanate-reactive polyol,
[0283] (c) optionally a chain extender and / or a cross-linking agent,
[0284] (d) flame retardants,
[0285] (e) optionally a filler,
[0286] (f) a blowing agent,
[0287] (g) a catalyst, and
[0288] (h) optionally additives and / or auxiliaries,
[0289] 4) mixing the polyol component obtained in step 3) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0290] 5) spraying or injecting the mixture obtained in step 4) onto the continuous phase reinforcing fibers provided on each side of the thermal insulation layer provided in step 2) through a first nozzle or injection head, and optionally spraying the discontinuous phase reinforcing fibers onto the continuous phase reinforcing fibers provided in step 2) through a second nozzle to obtain a sprayed or injected product;
[0291] 6) hot pressing the sprayed or injected product obtained in step 5) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0292] 7) demoulding and optionally trimming to obtain a laminated product comprising a polyurethane composite material disposed on each side of the thermal insulation layer;
[0293] The polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0294] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; and
[0295] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0296] For ease of understanding, Figure 6 An exemplary process for preparing a laminated product is presented.
[0297] In one embodiment, the reinforcing fibers in the discontinuous phase in step 4) are obtained by in-situ chopping long fibers and added to a mixture of isocyanate component and polyol component of polyurethane at a constant rate, and the length of the chopped reinforcing fibers is 6 to 100 mm.
[0298] In one embodiment, the reinforcing fibers in the continuous phase in step 1) are in the form of a mat, a woven fabric, or a combination thereof.
[0299] It should be noted that suitable materials for preparing the thermal insulation layer are the same as those described in Section II (Laminated Products). Suitable materials used in the above steps 2)-5) are the same as those described in Section I (PU Composite Materials). For the sake of brevity, they will not be repeated here.
[0300] Spray transfer molding (STM) process for preparing laminated products
[0301] In one aspect, the present invention relates to a spray transfer molding (STM) method for preparing a laminated product as described above, comprising the following steps:
[0302] 1) Provide thermal insulation by:
[0303] i) mixing the thermal insulation material with the binder,
[0304] ii) applying the mixture of step i) onto the substrate surface (for example by spraying or knife coating) and allowing the mixture to cure; and
[0305] iii) optionally removing the substrate;
[0306] 2) providing reinforcing fibers in the form of a continuous phase, the reinforcing fibers being arranged on each side of the thermal insulation layer obtained in step 1);
[0307] 3) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0308] (b) at least one isocyanate-reactive polyol,
[0309] (c) optionally a chain extender and / or a cross-linking agent,
[0310] (d) flame retardants,
[0311] (e) optionally a filler,
[0312] (f) a blowing agent,
[0313] (g) a catalyst, and
[0314] (h) optionally additives and / or auxiliaries,
[0315] 4) mixing the polyol component obtained in step 3) with the isocyanate component at a temperature of 20 to 80° C. to obtain a mixture;
[0316] 5) spraying the mixture obtained in step 4) onto the continuous phase reinforcing fibers provided on each side of the thermal insulation layer provided in step 2) through a first nozzle, and optionally spraying the discontinuous phase reinforcing fibers onto the continuous phase reinforcing fibers provided in step 2) through a second nozzle to obtain a sprayed product;
[0317] 6) hot pressing the sprayed product obtained in step 5) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0318] 7) demoulding and optionally trimming to obtain a laminated product comprising a polyurethane composite material disposed on each side of the thermal insulation layer;
[0319] The polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0320] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; and
[0321] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0322] It should be noted that, unless otherwise stated, all elements used in the "Spray Transfer Molding (STM) Method for Preparing PU Composite Materials" (such as but not limited to the raw materials used, environment (temperature, pressure, etc.), equipment or devices, and the order of steps) are also applicable to steps 2)-7 of the STM method for preparing laminated products. For the sake of brevity, they will not be repeated here.
[0323] Long Fiber Injection (LFI) process for producing laminated products
[0324] In another aspect, the present invention relates to a long fiber injection (LFI) method for preparing a laminated product as described above, comprising the following steps:
[0325] 1) Provide thermal insulation by:
[0326] i) mixing the thermal insulation material with the binder,
[0327] ii) applying the mixture of step i) onto the substrate surface (for example by spraying or knife coating) and allowing the mixture to cure; and
[0328] iii) optionally removing the substrate;
[0329] 2) providing reinforcing fibers in the form of a continuous phase, the reinforcing fibers being arranged on each side of the thermal insulation layer obtained in step 1);
[0330] 3) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C:
[0331] (b) at least one isocyanate-reactive polyol,
[0332] (c) optionally a chain extender and / or a cross-linking agent,
[0333] (d) flame retardants,
[0334] (e) optionally a filler,
[0335] (f) a blowing agent,
[0336] (g) a catalyst, and
[0337] (h) optionally additives and / or auxiliaries,
[0338] 4) mixing the polyol component obtained in step 3) with the isocyanate component and the reinforcing fiber in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture;
[0339] 5) injecting the mixture obtained in step 4) onto the reinforcing fibers in the form of a continuous phase provided on each side of the thermal insulation layer provided in step 2) through an injection head to obtain an injected product;
[0340] 6) hot pressing the injected product obtained in step 5) in a mold at a temperature of 40 to 180° C. and under a hot press clamping force of 100 to 2000 tons; and
[0341] 7) demoulding and optionally trimming to obtain a laminated product comprising a polyurethane composite material disposed on each side of the thermal insulation layer;
[0342] The polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material.
[0343] The reinforcing fibers contain 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; and
[0344] The reinforcing fibers are selected from glass fibers, basalt fibers, carbon fibers and natural fibers, preferably glass fibers and basalt fibers, and more preferably glass fibers.
[0345] It should be noted that, unless otherwise stated, all elements used in the "Long Fiber Injection (LFI) Method for Preparing PU Composite Materials" (such as but not limited to the raw materials used, environment (temperature, pressure, etc.), equipment or devices, and the order of steps) are also applicable to steps 2)-7 of the LFI method for preparing laminated products. For the sake of brevity, they will not be repeated here.
[0346] Surprisingly, it has been found that in the present application, the laminated product as described above or the laminated product prepared by the method as described above shows reduced weight, good mechanical strength, good flame retardancy, and at the same time good thermal insulation. In addition, the method is carried out in a robust and easy manner. Accordingly, the laminated product is obtained cost-effectively.
[0347] In yet another aspect, the present invention relates to a covering article suitable for a battery system, comprising the laminated product as described above or the laminated product prepared by the method as described above.
[0348] It should be noted that throughout the application, materials referred to in the method embodiments have the same meanings as those in the product embodiments, and unless otherwise stated, each of the general, preferred, more preferred and most preferred definitions and amounts of materials described in the product section also applies to the method of making the product and articles made from the product.
[0349] Example
[0350] The present invention will now be described with reference to Examples and Comparative Examples, which are not intended to limit the present invention.
[0351] General Description
[0352] The following starting materials were used in the examples:
[0353]
[0354]
[0355] The following methods are used to determine the properties:
[0356] In kg / m 3 Density of GB / T 6343-2008
[0357] Flammability UL94 V0
[0358] UL 94 5VA Standard
[0359] Tensile strength / modulus GB / T1447-2005
[0360] Flexural strength / modulus GB / T1449-2005
[0361] Example A: PU composite material
[0362] I. Preparation Examples
[0363] The PU composites of Examples 1 to 5 and Comparative Example 1 were prepared using the polyol components, isocyanate components and reinforcing fibers in the amounts defined in Table 1. The PU composite of Comparative Example 2 was commercially available from HUAYUAN ADV. MATERIALS under the trade name HY3102SMC, which was prepared by an existing sheet molding compound (SMC) process.
[0364] Table 1
[0365]
[0366]
[0367] *As mentioned above, fillers contained in the polyol component do not include reinforcing fibers.
[0368] Examples 1 to 3
[0369] The PU composite materials according to the present invention are each prepared by a long fiber injection (LFI) method, comprising the following steps.
[0370] The materials under the polyol component A as described in Table 1 were mixed to form the polyol component A. The materials under the isocyanate component B as described in Table 1 were mixed to form the isocyanate component B. The obtained polyol component A and the isocyanate component B were statically mixed under a pressure of 4 bar to obtain a mixture having a viscosity of about 200 mPa·s, and the reinforcing fibers were chopped and added to the obtained mixture under stirring to obtain a final mixture, wherein the length of the chopped reinforcing fibers was 15 mm. The final mixture was heated to about 650 g / m 2 The amount of 200 g / cm2 is injected into an open mold, which has been preheated at about 110°C and is designed with knives for cutting trimming and digging screw holes and allows the fixing of inserts (e.g. glass fiber mats and / or metal sheets, metal foils or solid flame retardant layers), in which 2 layers of glass fiber mats are placed. The mold is then closed and clamped at about 800 tons.
[0371] The part was molded for 5 minutes and then demoulded. A product with a thickness of about 1.8 mm was obtained.
[0372] As can be seen from Table 1, the ratio of the amount of the continuous and discontinuous reinforcing fibers used to the amount of the polyol component A and the isocyanate component B used as starting materials is (35-55):(45-65).
[0373] Examples 4 and 5
[0374] The PU composite materials according to the present invention are each prepared by a spray transfer molding (STM) method, comprising the following steps.
[0375] The materials under polyol component A as described in Table 1 were mixed and maintained at a pot temperature of 30°C to 40°C to prepare a polyol component A with reduced viscosity. The materials under isocyanate component B as described in Table 1 were mixed to form isocyanate component B. Polyol component A and isocyanate component B were impact mixed at a pressure of about 150 bar to obtain a mixture having a viscosity of about 500 mPa·s. The mixture was then heated at about 650 g / m 2 Spray the amount onto the surface of 2 layers of fiberglass mat.
[0376] The resulting PU with glass fibers is placed by a robot at about atmospheric pressure onto an open mold that has been preheated at about 110°C and is designed with tools for cutting trims and digging screw holes, and allowing the fixing of inserts (e.g., glass fiber mats and / or metal sheets, metal foils or solid flame retardant layers), and the mold is then closed and clamped at about 500 tons.
[0377] The part was molded for 5 minutes and then demoulded. A product with a thickness of about 1.8 mm to 2.4 mm was obtained.
[0378] Comparative Example 1
[0379] A PU composite material was prepared by the same method as described in Examples 1 to 3. A product having a thickness of about 1.4 mm was obtained.
[0380] II. Effects of the Embodiment
[0381] Performance testing of PU composite products
[0382] The physical and chemical properties of the PU composite product of the preparation example are listed in Table 2.
[0383] Table 2
[0384]
[0385]
[0386] Examples 6 to 7 - Electromagnetic shielding performance test of covered products
[0387] Covered articles of Example 6 and Example 7 were prepared respectively comprising the PU composite materials of Example 2 and Example 4. The cover articles contained a PU composite sheet as a core layer, and an aluminum alloy sheet with a thickness of 0.2 mm located on one side of the core layer.
[0388] The electromagnetic shielding performance of these covered products was tested. The results are listed in Table 3.
[0389] Table 3
[0390] sample Example 6 Example 7 E0 / E1 1000:1 10,000:1 SE[dB] 60 80
[0391] Examples 8 to 10 - Fire resistance test of battery pack
[0392] Battery packs of Examples 8 to 10 were prepared, each including the cover articles of Examples 3 to 5. Each battery pack included a cover article and a bottom tray. The bottom tray was made of a stamped aluminum alloy sheet.
[0393] The fire resistance of these battery packs was tested. The results are listed in Table 4.
[0394] External combustion test: GB 38031-2020
[0395] ■Test method: (8.2.7.1)
[0396] ■ Ignite the fuel tray from a distance of ≥3m from the target
[0397] Preheat the fire for 60 seconds
[0398] ■Move the fuel tray under the battery pack
[0399] ■ Expose the battery pack directly to fire for 70 seconds
[0400] ■Add the cover to the fuel pan and continue testing for 60 seconds
[0401] ■Remove the fuel tray
[0402] ■Observe the battery pack for 2 hours
[0403] ■Requirement: (5.2.7)
[0404] ■Battery packs should not explode
[0405] ■No nickel-metal hydride batteries used
[0406] Table 4
[0407] sample Example 8 Example 9 Example 10 Burning test pass pass pass
[0408] It can be seen from Table 3 that the covering product containing the PU composite material according to the present invention has good EMI shielding performance.
[0409] It can be seen from Table 4 that the battery pack containing the covering article according to the present invention as the upper cover passed the external combustion test.
[0410] Examples 11 to 13 - Voltage Withstand Test
[0411] The covered product of Example 11 comprises two layers of the PU composite material of Example 4, which are hot pressed together. The covered product of Example 12 comprises a layer of the PU composite material of Example 4 and a layer of steel sheet (thickness = 0.2 mm) placed on one side of the PU composite material. The covered product of Example 13 comprises a layer of steel sheet (thickness = 0.2 mm) and two layers of the PU composite material of Example 4 placed on both sides of an aluminum alloy sheet.
[0412] To evaluate their voltage resistance performance, the covered articles of Examples 11-13 were tested at a high DC voltage (3000V) for 60 seconds. Then, the covered articles were burned at 1000°C for 30 minutes. For the covered article of Example 12, the PU composite material side was burned. And the burned covered articles of Examples 11-13 were tested again at a high DC voltage (3000V or 1000V) for 60 seconds.
[0413] The test results are shown in Table 5 below. It should be noted that the covered articles of Examples 11-13 before being burned showed a leakage current of less than 3 mA at a voltage of 3000 V. The covered article of Example 12 after being burned showed a leakage current of less than 3 mA at a voltage of 1000 V, and the covered articles of Examples 11 and 13 further showed a leakage current of less than 3 mA even at a voltage of 3000 V. In addition, none of the covered articles of Examples 11-13 showed electrical breakdown or arcing.
[0414] These test results show that the covered articles of Examples 11-13 have excellent voltage resistance and electrical insulation properties, which makes them particularly suitable as covers / casings for battery systems.
[0415] Table 5
[0416]
[0417]
[0418] Example B: Laminated Product
[0419] I. Preparation Examples
[0420] Examples 14 to 17: Preparation of intumescent insulation layer
[0421] The intumescent thermal insulation layers of Examples 14 and 15 were prepared using the amounts of polyol component, isocyanate component and intumescent component as defined in Table 6.
[0422] Table 6
[0423]
[0424]
[0425] Embodiment 14
[0426] The preparation of the intumescent thermal insulation layer according to the present invention by spraying technology comprises the following steps.
[0427] The materials under polyol component A' as described in Table 6 were mixed to form polyol component A'. The materials under isocyanate component B' as described in Table 6 were mixed to form isocyanate component B'. Expandable graphite was premixed into polyol component A' and maintained at a pot temperature of 30°C to 40°C to obtain a premixed mixture. The premixed mixture and isocyanate component B' were mixed at a pressure of about 10 bar to obtain a mixture. The mixture was then sprayed onto release paper in an amount to obtain a surface density of about 100 g / m 2 The intumescent insulation layer is also referred to as an "IL100" layer.
[0428] Then, the release paper with the intumescent thermal insulation material was heated and cured in an oven at about 100° C. for 5 minutes, and then the intumescent thermal insulation layer was removed from the release paper.
[0429] Embodiment 15
[0430] The intumescent thermal insulation layer according to the invention is produced by a knife coating technique.
[0431] The materials under polyol component A' as described in Table 6 were mixed to form polyol component A'. The materials under isocyanate component B' as described in Table 6 were mixed to form isocyanate component B'. The expansion component including APP 422, melamine, pentaerythritol and kaolin was premixed into polyol component A' and maintained at a pot temperature of 30°C to 40°C to obtain a premixed mixture. The premixed mixture and isocyanate component B' were impact mixed at a pressure of about 150 bar to obtain a mixture. The mixture was then knife coated onto release paper in an amount to obtain a surface density of about 100 g / m 2 The intumescent insulation layer is also referred to as the "IL100-2" layer.
[0432] Then, the release paper with the intumescent thermal insulation material was heated and cured in an oven at about 100° C. for 5 minutes, and then the intumescent thermal insulation layer was removed from the release paper.
[0433] The intumescent insulation layers of Examples 16 and 17 were prepared by the same method as described in Example 14, except that the spray and knife coating amounts were changed to obtain a surface density of about 150 g / m 2 and 230g / m 2 Intumescent insulation, also known as "IL150" or "IL230".
[0434] Examples 18-23: Preparation of Laminated Products
[0435] The laminated product of Example 18 was prepared by a spray transfer molding (STM) method, comprising the following steps.
[0436] like Figure 6 As shown, an intumescent thermal insulation layer of Example 14 (ie, IL100) is provided, and two layers of glass fiber mats are placed on both sides of the intumescent thermal insulation layer.
[0437] The materials under polyol component A as described in Example 4 of Table 1 were mixed and maintained at a pot temperature of 30°C to 40°C to prepare a polyol component A with reduced viscosity. The materials under isocyanate component B as described in Example 4 of Table 1 were mixed to form isocyanate component B. Polyol component A and isocyanate component B were impact mixed at a pressure of about 150 bar to obtain a mixture having a viscosity of about 500 mPa·s. The mixture was then heated at about 650 g / m 2 The amount of spray is applied to the glass fiber mat (surface density = 750g / m 2 ) on the surface. The mixture is about 650g / m 2 The amount of spray is applied to the glass fiber mat (surface density = 200 g / m 2 )superior.
[0438] The resulting product comprising an intumescent thermal insulation layer and two layers of polyurethane composite material disposed on each side of the intumescent thermal insulation layer is placed by a robot at about atmospheric pressure onto an open mold that has been preheated at about 110° C. and is designed with knives for cutting trims and digging screw holes, and allows the fixing of inserts (e.g., metal sheets or metal foils), and then the mold is closed and clamped at about 500 tons.
[0439] The part was molded for 5 minutes and then demoulded. A laminated product was obtained, which is also known as GF750 / IL100 / GF200.
[0440] The laminated products of Examples 19 and 20 were prepared by the same method as described in Example 18, except that Example 19 used the intumescent insulation layer of Example 16 (i.e., "IL150"), and Example 20 used the intumescent insulation layer of Example 17 (i.e., "IL230"). The laminated products of Examples 21 and 22 were prepared by the same method as described in Example 18, except that the surface density of the glass fiber mat was changed as shown in Table 7.
[0441] The laminated product of Example 23 was prepared by the same method as Example 18, except that its intumescent insulation layer was prepared according to Example 15 (ie, IL100-2).
[0442] Comparative Example 3:
[0443] The product of Comparative Example 3 was prepared by the same method as described in Example 18, except that no intumescent insulation layer was provided. This product is referred to as GF750 / GF200.
[0444] II. Effects of the Embodiment
[0445] The laminated products prepared according to Examples 18-23 and Comparative Example 3 were fire tested at 1300° C. for 10 minutes on one side ( T1 ). The temperature on the opposite side was recorded as T2 as shown in Table 7.
[0446] Table 7
[0447]
[0448] As shown in Table 7 above, the laminated products (Examples 18-23) prepared according to the present application show excellent thermal insulation performance because the temperature T2 of the opposite side is lower than 400°C. In particular, the T2 of Examples 18-22 is even lower than 320°C.
[0449] To evaluate the voltage resistance of the laminated product, the laminated product of Example 22 was tested at a high DC voltage (3000V) for 60 seconds. Then, the laminated product was burned at 1000°C for 30 minutes. The burned covered product of Example 22 was tested again at a high DC voltage (3000V) for 60 seconds.
[0450] The test results are shown in Table 8 below. It should be noted that the laminated product of Example 22 before and after being fired showed a leakage current of less than 3 mA at a voltage of 3000 V. In addition, it did not show electrical breakdown or arcing.
[0451] These test results indicate that the laminated product of Example 22 has excellent voltage resistance and electrical insulation properties, which makes it particularly suitable as a cover / casing for a battery system.
[0452] Table 8
[0453]
[0454] The structures, materials, components, compositions and methods described herein are intended to be representative examples of the present invention, and it should be understood that the scope of the present invention is not limited by the scope of the examples. Those skilled in the art will recognize that the present invention can be practiced by changes to the disclosed structures, materials, compositions and methods, and these changes are considered to be within the scope of the present invention. Therefore, the present invention is intended to cover these modifications and changes within the scope of the appended claims and their equivalents.
Claims
1. A method for preparing a polyurethane composite material for a battery system covering product, wherein the thickness of the polyurethane composite material is 0.5 to 10 mm, the method comprising the following steps: 1) providing reinforcing fibers in the form of a continuous phase; 2) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C: (b) at least one isocyanate-reactive polyol, (c) optionally a chain extender and / or a cross-linking agent, (d) flame retardants, (e) optionally a filler, (f) a blowing agent, (g) a catalyst, and (h) optionally additives and / or auxiliaries, 3) mixing the polyol component obtained in step 2) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture; 4) spraying or injecting the mixture obtained in step 3) onto the reinforcing fibers in the continuous phase provided in step 1) through a first nozzle or an injection head, and optionally spraying the reinforcing fibers in the discontinuous phase onto the reinforcing fibers in the continuous phase provided in step 1) through a second nozzle to obtain a sprayed or injected product; 5) closing the mold and maintaining the temperature at 40 to 180° C., and hot pressing the sprayed or injected product obtained in step 4) under a hot pressing clamping force of 100 to 2000 tons; and 6) demoulding and optional trimming; The polyurethane composite material obtained in step 6) comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material, The reinforcing fibers comprise 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; The reinforcing fibers in the continuous phase have a density of 400 to 1600 g / m2; as well as The reinforcing fibers in the continuous phase are selected from glass fibers, basalt fibers and carbon fibers.
2. The method according to claim 1, wherein the reinforcing fibers in the discontinuous phase form in step 3) are obtained by in-situ short-cutting long fibers and added to a mixture of an isocyanate component and a polyol component of a polyurethane at a constant rate, and the length of the short-cut reinforcing fibers is 6 to 100 mm.
3. The method according to claim 1 or 2, wherein the reinforcing fibers are selected from glass fibers and basalt fibers. The method according to claim 3 , wherein the reinforcing fibers are glass fibers.
5. The method according to claim 1 or 2, wherein the reinforcing fiber is impregnated in the polyurethane foam.
6. The method according to claim 1 or 2, wherein the reinforcing fibers in the continuous phase in step 1) are in the form of a mat, a woven fabric or a combination thereof.
7. The method of claim 6, wherein the polyurethane composite material comprises 1 to 4 layers of a mat, a woven fabric, or a combination thereof.
8. The method according to claim 1 or 2, wherein the reinforcing fibers in the form of the discontinuous phase have a length of 6 to 100 mm.
9. The method according to claim 1 or 2, wherein the density of the polyurethane composite material is less than 2.2 g / cm 3 .
10. The method according to claim 1 or 2, wherein the polyurethane composite material comprises a flame retardant (d) selected from the group consisting of tris(2-chloroisopropyl) phosphate, melamine, expandable graphite EG, red phosphorus, ammonium polyphosphate, tris(1-chloro-2-propyl) phosphate TCPP, triethyl phosphate TEP, chlorine- and bromine-containing polyols, epichlorohydrin, chlorendic anhydride, trichlorobutylene oxide TCBO, phosphorus-containing polyols, orthophosphates and phosphites.
11. The method of claim 10, wherein the phosphorus-containing polyol is selected from the group consisting of phosphonate polyols, phosphine oxide polyols, and phosphoramidite polyols.
12. The method according to claim 1 or 2, wherein the polyurethane composite material passes the fire test of UL94 V0 level.
13. A covering article comprising the polyurethane composite material obtained according to the method of any one of claims 1 to 12.
14. The cover article of claim 13, further comprising at least one metal sheet located on at least one side of the polyurethane composite.
15. The cover article of claim 14 comprising two metal sheets on each side of the polyurethane composite.
16. The covered article according to claim 13 or 14, wherein the metal sheet is selected from the group consisting of aluminum alloy, iron, steel and aluminum sheet.
17. The covered article according to claim 13 or 14, wherein the metal sheet has a thickness of 0.08 to 1.2 mm.
18. The covered article according to claim 13 or 14, wherein the metal sheet has a thickness of 0.2 to 1.2 mm.
19. The covered article according to claim 18, wherein the metal sheet has a thickness of 0.5 to 1.0 mm.
20. A laminate product for a battery system cover article, wherein the laminate product comprises at least one thermal insulation layer; and at least two layers of a polyurethane composite material prepared according to the method of any one of claims 1 to 12, which are arranged on each side of the thermal insulation layer; The thermal insulation layer comprises an adhesive and a thermal insulation material, wherein the thermal insulation material is distributed in the adhesive.
21. The laminate product of claim 20, wherein the thermal insulation layer comprises 10 wt% to 70 wt% of the thermal insulation material, based on the total weight of the thermal insulation layer.
22. The laminate product of claim 21, wherein the thermal insulation layer comprises 20 wt% to 50 wt% of the thermal insulation material, based on the total weight of the thermal insulation layer.
23. The laminate product according to claim 20, wherein the surface density of the thermal insulation layer is 50 g / m 2 Up to 500g / m 2 .
24. The laminate product according to claim 20, wherein the thermal insulation layer is an intumescent thermal insulation layer, the thermal insulation material is an intumescent thermal insulation material, and the intumescent thermal insulation material is selected from phosphorus-containing materials, nitrogen-containing materials, sulfur-containing materials, boron-containing materials, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, expandable graphite EG, pentaerythritol, kaolin, or a combination thereof.
25. The laminated product according to claim 24, wherein the average particle size of the expandable graphite is 50 to 500 μm.
26. The laminate product of claim 20, wherein the adhesive is selected from the group consisting of polyurethane, epoxy, polyethylene, polypropylene, polystyrene, or combinations thereof.
27. The laminate product of claim 26, wherein the adhesive is a polyurethane, the polyurethane being the reaction product of a reaction mixture comprising an isocyanate and an isocyanate-reactive polyol, wherein the isocyanate-reactive polyol comprises a polyol having a weight average molecular weight of 1,000 to 10,000.
28. The laminated product of claim 27, wherein the isocyanate-reactive polyol comprises a polyol having a weight average molecular weight of 4,000 to 6,000.
29. The laminate product of claim 27, wherein the isocyanate-reactive polyol has a functionality of 2 to 3.
30. The laminated product of claim 20, wherein the laminated product has an expansion ratio of 5 to 20.
31. The laminate product according to claim 20, wherein the laminate product further comprises at least one substrate layer disposed between the thermal insulation layer and the polyurethane composite material layer, the substrate layer comprising a fiber sheet, a plastic sheet, and a metal sheet.
32. The laminate product of claim 20 or 31, wherein the laminate product further comprises at least one metal sheet located on a side of the laminate product.
33. A method of preparing a laminated product according to any one of claims 20 to 32, the method comprising the steps of: 1) Provide thermal insulation by: i) mixing the thermal insulation material with the binder, ii) applying the mixture of step i) onto a substrate surface and allowing the mixture to cure; and iii) optionally removing the substrate; 2) providing reinforcing fibers in the form of a continuous phase, the reinforcing fibers being arranged on each side of the thermal insulation layer obtained in step 1); 3) Prepare the polyol component by mixing the following materials in a tank at a temperature of 20 to 80°C: (b) at least one isocyanate-reactive polyol, (c) optionally a chain extender and / or a cross-linking agent, (d) flame retardants, (e) optionally a filler, (f) a blowing agent, (g) a catalyst, and (h) optionally additives and / or auxiliaries, 4) mixing the polyol component obtained in step 3) with an isocyanate component and optionally reinforcing fibers in the form of a discontinuous phase at a temperature of 20 to 80° C. to obtain a mixture; 5) spraying or injecting the mixture obtained in step 4) onto the continuous phase reinforcing fibers provided on each side of the thermal insulation layer provided in step 2) through a first nozzle or injection head, and optionally spraying the discontinuous phase reinforcing fibers onto the continuous phase reinforcing fibers provided in step 2) through a second nozzle to obtain a sprayed or injected product; 6) closing the mold and maintaining the temperature at 40 to 180° C., and hot pressing the sprayed or injected product obtained in step 5) under a hot pressing clamping force of 100 to 2000 tons; and 7) demoulding and optionally trimming to obtain a laminated product comprising a polyurethane composite material disposed on each side of the thermal insulation layer; The polyurethane composite material comprises 35 to 75 wt % of reinforcing fibers and 25 to 65 wt % of polyurethane foam, based on the total weight of the polyurethane composite material. The reinforcing fibers comprise 75 to 100 wt % of reinforcing fibers in a continuous phase and 0 to 25 wt % of reinforcing fibers in a discontinuous phase, based on the total weight of the reinforcing fibers; The reinforcing fibers in the continuous phase have a density of 400 to 1600 g / m2; as well as The reinforcing fibers in the continuous phase are selected from glass fibers, basalt fibers and carbon fibers.
34. The method of claim 33, wherein the reinforcing fibers are selected from glass fibers and basalt fibers.
35. The method of claim 34, wherein the reinforcing fibers are glass fibers.
36. The method according to claim 33, wherein the reinforcing fibers in the discontinuous phase form in step 4) are obtained by in-situ chopping long fibers and added to a mixture of an isocyanate component and a polyol component of a polyurethane at a constant rate, and the length of the chopped reinforcing fibers is 6 to 100 mm.
37. The method of claim 33, wherein the reinforcing fibers in the continuous phase in step 1) are in the form of a mat, a woven fabric, or a combination thereof.
38. A covering article suitable for a battery system, comprising a laminate product according to any one of claims 20 to 32 or a laminate product prepared by a method according to any one of claims 33 to 37.
